2015
DOI: 10.1139/cjz-2014-0266
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cues modulating electrophysiological and behavioural responses in the parasitic waspCotesia sesamiae

Abstract: A better understanding of the chemical cues employed by parasitoids to locate their herbivore hosts will contribute towards effective exploitation of parasitoids as biological control agents against damaging crop pests. The current study was conducted to establish key bioactive compounds mediating behavioural response in the parasitic wasp Cotesia sesamiae (Cameron, 1906) (Hymenoptera: Braconidae) by employing electrophysiological techniques and behavioural studies. Electroantennogram (EAG) recording with synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
0
31
1
Order By: Relevance
“…Odorants in the surrounding environment are detected by olfactory sensilla mainly distributed on the antennae. Electrophysiological studies using electroantennograms (EAGs) and single sensillum recordings revealed that the olfactory sensory neurones in the antennal sensilla of parasitoids respond to certain HIPV components (Dweck et al ., ; Tamiru et al ., ). Odorant receptors (ORs) function with well‐conserved odorant coreceptors (ORcos) in the dendrites of olfactory sensory neurones to determine the sensitivity and specificity of olfactory reception (Larsson et al ., ; Benton et al ., ; Hallem and Carlson, ).…”
Section: Introductionmentioning
confidence: 97%
“…Odorants in the surrounding environment are detected by olfactory sensilla mainly distributed on the antennae. Electrophysiological studies using electroantennograms (EAGs) and single sensillum recordings revealed that the olfactory sensory neurones in the antennal sensilla of parasitoids respond to certain HIPV components (Dweck et al ., ; Tamiru et al ., ). Odorant receptors (ORs) function with well‐conserved odorant coreceptors (ORcos) in the dendrites of olfactory sensory neurones to determine the sensitivity and specificity of olfactory reception (Larsson et al ., ; Benton et al ., ; Hallem and Carlson, ).…”
Section: Introductionmentioning
confidence: 97%
“…Successful location of oviposition sites by parasitoids requires the ability to perceive physical and chemical cues that indicate the presence of resources (Schröder & Hilker, ). It is widely accepted that chemical stimuli, such as infochemicals, are of great value for parasitoid foraging and survival (Tamiru et al., ; Avila et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants can emit complex blends of volatile chemical compounds from various organs in response to pest attack. These volatiles are commonly used by natural enemies as cues to seek prey and locate hosts (Tan & Liu, ; Tamiru et al., ; Penaflor et al., ). In the study conducted by Lou et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the volatile profiles display an enormous range of diversity among plant species, different plant taxa exhibited a considerable overlap in production of HIPVs [5,17]. Most HIPVs could fall into the following major categories (in order of decreasing size): terpenoids (e.g., (E)-β-ciemene, (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), (E,E)-α-farnesene), fatty acid derivatives including lipoxygenase pathway products (e.g., hexanal, (Z)-3-hexen-l-ol, (Z)-3-hexenyl acetate), benzenoids/phenylpropanoids (e.g., methyl salicylate, methyl eugenol, indole), C 5 -branched compounds, and various nitrogen-and sulphur-containing compounds (e.g., isothiocyanates or nitriles, respectively) [3,17].…”
Section: Herbivore Induced Plant Volatile Compounds (Hipvs)mentioning
confidence: 99%